Lack of association between bridging integrator 1 (BIN1) rs744373 polymorphism and tau‐PET load in cognitively intact older adults - Jolien Schaeverbeke; Emma S Luckett; Silvy Gabel; Mariska Reinartz; Steffi De Meyer; Isabelle Cleynen; Kristel Sleegers; Christine Van Broeckhoven; Guy Bormans; Kim Serdons; Koen Van Laere; Patrick Dupont; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2022)
Abstract Introduction The bridging integrator 1(BIN1) rs744373 risk polymorphism has been linked to increased [18F]AV1451 signal in non‐demented older adults (ie., mild cognitive impairment [MCI] plus cognitively normal [CN] individuals). However, the association of BIN1 with in vivo tau, amyloid beta (Aβ) burden, and cognitive impairment in the asymptomatic stage of Alzheimer's disease (AD) remains unknown. Methods The BIN1 effect on [18F]AV1451 binding was evaluated in 59 cognitively normal (CN) participants (39% apolipoprotein E [APOE ε4]) from the Flemish Prevent AD Cohort KU Leuven (F‐PACK), as well as in 66 Alzheimer's Disease Neuroimaging Initiative (ADNI) CN participants, using voxelwise and regional statistics. For comparison, 52 MCI patients from ADNI were also studied. Results Forty‐four percent of F‐PACK participants were BIN1 rs744373 risk‐allele carriers, 21% showed high amyloid burden, and 8% had elevated [18F]AV1451 binding. In ADNI, 53% and 50% of CNs and MCIs, respectively, carried the BIN1 rs744373 risk‐allele. Amyloid positivity was present in 23% of CNs and 51% of MCIs, whereas 2% of CNs and 35% of MCIs showed elevated [18F]AV1451 binding. There was no significant effect of BIN1 on voxelwise or regional [18F]AV1451 in F‐PACK or ADNI CNs, or in the pooled CN sample. No significant association between BIN1 and [18F]AV1451 was obtained in ADNI MCI patients. However, in the MCI group, numerically higher [18F]AV1451 binding was observed in the BIN1 risk‐allele group compared to the BIN1 normal group in regions corresponding to more progressed tau pathology. Discussion We could not confirm the association between BIN1 rs744373 risk‐allele and elevated [18F]AV1451 signal in CN older adults or MCI. Numerically higher [18F]AV1451 binding was observed, however, in the MCI BIN1 risk‐allele group, indicating that the previously reported positive effect may be confounded by group. Therefore, when studying how the BIN1 risk polymorphism influences AD pathogenesis, a distinction should be made between asymptomatic, MCI, and dementia stages of AD.